Spracheinstellungen und Identitätskonstruktion Eine gesprächsanalytische Untersuchung sprachbiographischer Interviews mit Deutsch-Vietnamesen - König, Katharina (Empirische Linguistik / Empirical Linguistics, 2014)
This study examines statements about language attitudes expressed by bilingually raised Germans of Vietnamese origin during language biographical interviews in search of specific conversational features. A further focus of the research is on the linguistic construction of different "language spaces" in which the interviewees position themselves as multilingual individuals.